Measurement of the Top Quark Mass in the All-Hadronic Mode at CDF - Collaboration, CDF; Aaltonen, T; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; et al. (2011)
We present a measurement of the top quark mass (Mtop) in the all-hadronic decay channel using 5.8 fb^{-1} of proton-antiproton data collected with the CDF II detector at the Fermilab Tevatron Collider. Events with 6 to 8 jets are selected by a neural network algorithm and by the requirement that at least one of the jets is tagged as a b quark jet. The measurement is performed by a likelihood fit technique, which determines simultaneously Mtop and the jet energy scale (JES) calibration. The fit yields a value of 172.5 +- 1.4(stat) +-1.0(JES) +-1.1(syst) GeV/c^2.